Penilaian Kapabilitas Tata Kelola Teknologi Informasi Menggunakan Kerangka Kerja Cobit 2019 dengan Fokus Domain APO pada RSPAU Dr. Suhardi Hardjolukito - Arimurti, Nurfadhilah Azzahra; Nurtrisha, Widyatasya Agustika; Falahah, Falahah (Universitas Merdeka Malang, 2024)
The development of information technology has had a significant impact on human life. Currently, information technology has become an important thing for an organization. This is because the existence of IT helps increase the effectiveness of an organization's business processes. RSPAU dr. S. Hardjolukito is the Air Force Central Hospital located in Yogyakarta. RSPAU Hardjolukito utilizes IT to support health service activities. In implementing IT in hospitals, IT governance performance must be evaluated so that every IT management runs well. The problem that RSPAU Hardjolukito has is that IT management has not been fully implemented in the hospital. This research aims to evaluate gaps and provide recommendations for potential improvements in IT governance to improve hospital quality. The research method used is a qualitative method approach by conducting interviews. The research was conducted using the COBIT 2019 framework with a focus on the APO11 and APO12 domains. The recommendation based on the results of the capability assessment in the Managed Quality APO11 process is to ensure that the quality of hospital quality management can be managed and identified well. Meanwhile, the recommendation in the Manage Risk APO12 process is to ensure that the risks faced by the hospital can be managed and identified properly and to create a risk profile document according to hospital regulations. With these recommendations, it is hoped that RSPAU Dr. S. Hardjolukito will be able to improve the quality of IT quality management and manage risk profiles.